Questionnaire Design and Validation to Measure the Effectiveness of the Outcome-Based Teaching-Learning Process - Jyotiprava Mohanta; Shyamal Kumar Das Mandal (Scientia Publica Media, 2026)
In outcome-based education, the learners know what is expected of them after the course completion. The learners here are responsible for their learning process, which increases their active learning, self-learning, collaborative learning, higher-order skills, and, in turn, life-long learning skills. This paper is designed to develop a questionnaire that measures domain-dependent and domain-independent skills like self-learning, active and collaborative learning, higher-order thinking, and the learners’ satisfaction and continuous updating of the curriculum for the proposed outcome-based teaching-learning process. It also serves as a template for the steps needed to design and validate a questionnaire. During the design of the questionnaire, the content validity was established by five experts, and the CVI value of the items considered was ≥ 0.80. After designing the questionnaire, the proposed methodology was implemented and validated on the undergraduate BTech learners of “Seemanta Engineering College” as a pilot study. The preliminary and factor analysis results were applied to 220 learners, and the results were significant. The confirmatory results (RMSEA = 0.049, CFI = 0.963, TLI = 0.957, and SRMR = 0.036), considering 436 learners, also validate that the designed questionnaire is reliable and valid to measure the effectiveness of the teaching-learning process. This paper will guide the researcher step by step to design and validate the questionnaire, thus improving the quality of research.